Parametrization of Deceleration Parameter in f(Q) Gravity - Gaurav N. Gadbail; Sanjay Mandal; Pradyumn Kumar Sahoo (Physics, 2022)
In this paper, we investigate the modified symmetric teleparallel gravity or <semantics>f(Q)</semantics> gravity, where Q is the nonmetricity, to study the evolutionary history of the universe by considering the functional form of <semantics>f(Q)=αQn</semantics>, where <semantics>α</semantics> and n are constants. Here, we consider the parametrization form of the deceleration parameter as <semantics>q=q0+q1<mspace width="0.166667em"></mspace>z/(1+z)2</semantics> (with the parameters <semantics>q0</semantics><semantics>(q</semantics> at <semantics>z=0)</semantics>, <semantics>q1</semantics>, and the redshift, z), which provides the desired property for a sign flip from a decelerating to an accelerating phase. We obtain the solution of the Hubble parameter by examining the mentioned parametric form of q, and then we impose the solution in Friedmann equations. Employing the Bayesian analysis for the Observational Hubble data (OHD), we estimated the constraints on the associated free parameters <semantics>(H0,q0,q1)</semantics> with <semantics>H0</semantics> the current Hubble parameter to determine if this model may challenge the <semantics>Λ</semantics>CDM (<semantics>Λ</semantics> cold dark matter with the cosmological constant, <semantics>Λ</semantics>) limitations. Furthermore, the constrained current value of the deceleration parameter <semantics>q0=−0.<msubsup>832−0.091+0.091</msubsup></semantics> shows that the present universe is accelerating. We also investigate the evolutionary trajectory of the energy density, pressure, and EoS (equation-of-state) parameters to conclude the accelerating behavior of the universe. Finally, we try to demonstrate that the considered parametric form of the deceleration parameter is compatible with <semantics>f(Q)</semantics> gravity.